2008
DOI: 10.1063/1.2973629
|View full text |Cite
|
Sign up to set email alerts
|

The H3+ rovibrational spectrum revisited with a global electronic potential energy surface

Abstract: In this paper, we have computed the rovibrational spectrum of the H(3) (+) molecule using a new global potential energy surface, invariant under all permutations of the nuclei, that includes the long range electrostatic interactions analytically. The energy levels are obtained by a variational calculation using hyperspherical coordinates. From the comparison with available experimental results for low lying levels, we conclude that our accuracy is of the order of 0.1 cm(-1) for states localized in the vicinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
120
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(126 citation statements)
references
References 63 publications
3
120
0
3
Order By: Relevance
“…We have improved our previous study 24 by employing a larger (and converged) nuclear statistics, and investigated the effect of the accuracy of the H + 3 PES parametrization on dynamical results by using the pioneering parametrization of Giese and Gentry, 27 V GG , and the most recent one of Velilla et al, 28 V VLA . We have found that inelastic cross sections are indeed sensitive to the accuracy of the PES from low (few eV) to intermediate (100 eV) impact energies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have improved our previous study 24 by employing a larger (and converged) nuclear statistics, and investigated the effect of the accuracy of the H + 3 PES parametrization on dynamical results by using the pioneering parametrization of Giese and Gentry, 27 V GG , and the most recent one of Velilla et al, 28 V VLA . We have found that inelastic cross sections are indeed sensitive to the accuracy of the PES from low (few eV) to intermediate (100 eV) impact energies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, V GG has been originally designed to describe H + +H 2 collisions without rearrangement; in the case of nuclear exchange and dissociation processes, ρ and R are redefined during the collision. This is not necessary when using the PES of Velilla et al, 28 V VLA . This PES is constructed on DIM grounds, but all long-range terms are included in the diagonal elements of the DIM matrix, yielding a global potential function symmetric under any permutation of the three identical nuclei.…”
Section: Nuclear Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PES by Velilla et al [35], which includes the LR interactions in the functional form, satisfies the first requirement. The dominant contributions involve the charge quadrupole, ∝ − R −3 , and the charge-induced dipole, ∝−R −4 , interactions.…”
mentioning
confidence: 98%
“…New statistical calculations are also performed in order to test the possible statistical behavior of the H þ þ H 2 reaction. First, accurate three-dimensional quantum dynamics calculations have been performed on a recently published ab initio PES [12] that is rigorously symmetric under any permutation of the three identical atoms. It presents a deep well (4.6 eV relative to the H þ þ H 2 asymptote) and no barrier in the entrance channel.…”
mentioning
confidence: 99%